2017
DOI: 10.3390/pharmacy5040057
|View full text |Cite
|
Sign up to set email alerts
|

Role of Information Anxiety and Information Load on Processing of Prescription Drug Information Leaflets

Abstract: In this study, we evaluate the role of information anxiety and information load on the intention to read information from prescription drug information leaflets (PILs). These PILs were developed based on the principals of information load and consumer information processing. This was an experimental prospective repeated measures study conducted in the United States where 360 (62% response rate) university students (>18 years old) participated. Participants were presented with a scenario followed by exposure to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…As time goes on, consumers may have information anxiety in common. And Shweta et al (2017) confirmed that people often contact with massive certain information, and over time, people would find that they have common information anxiety characteristics. Ruiz Mafé and Sanz Blas (2006) found that the information that consumers are exposed to through various information channels can affect their perceived values and behavior.…”
Section: The Effect Of Information Anxiety On Perceived Values and Purchase Behaviormentioning
confidence: 75%
See 1 more Smart Citation
“…As time goes on, consumers may have information anxiety in common. And Shweta et al (2017) confirmed that people often contact with massive certain information, and over time, people would find that they have common information anxiety characteristics. Ruiz Mafé and Sanz Blas (2006) found that the information that consumers are exposed to through various information channels can affect their perceived values and behavior.…”
Section: The Effect Of Information Anxiety On Perceived Values and Purchase Behaviormentioning
confidence: 75%
“…The items used a 5-point Likert scale ranging from "1 = strongly disagree" to "5 = strongly agree" (see Appendix A). Five items of information anxiety were adapted from Zung (1971) and Shweta et al (2017); four items of uncertainty were adapted from Kushwah et al (2019b); four items of sustainable consumption attitude were adapted from Arvola et al (2008) and Dean et al (2012); seven items of functional value were adapted Kushwah et al (2019a) and Akbar et al (2019); three items of health value were adapted from Rahnama (2016); four items of environmental value were adapted from Biswas and Roy (2015); and the three items of purchase behavior were adapted from Michaelidou and Hassan (2008) and Singh and Verma (2017).…”
Section: Methodsmentioning
confidence: 99%
“…The survey consisted of 30 close-ended questions with answers of yes/no/I am not sure, categorized into four parts: (i) demographic characteristics of the student; (ii) basic and clinical PGx knowledge; (iii) exposure to PGx education; (iv) attitudes towards PGx. Some of these questions were adopted from similar studies that were undertaken in the USA,21 Zimbabwe22 and Bosnia and Herzegovina,12 with some modifications being made to make the questionnaire easier to understand by pharmacy students. In addition, we developed other questions which could help assessment of PGx knowledge, such as exposure to PGx education and PGx knowledge.…”
Section: Methodsmentioning
confidence: 99%
“…For example, ( Lee, Kim & Koh, 2016 b) found that the level of attention to news through social media was significantly associated with the perceived news information overload which further was related to psychological stress and negative emotion (anxiety). In the context of health information, consumer's engagement with multiple information sources increases the likelihood of information overload and information anxiety ( Bapat, Patel, & Sansgiry, 2017 ). Therefore, it is assumed that the frequency of different information sources exposure is a stimulus that directly affects the individual's state of information anxiety in the COVID-19 context as well, and the following possible relationships are proposed: H3a: Individuals who report more frequent 'Personal Network' sources exposure will perceive a higher level of information anxiety H3b: Individuals who report more frequent 'Mass Media' sources exposure will perceive a higher level of information anxiety H3c: Individuals who report more frequent 'Print Media' sources exposure will perceive a higher level of information anxiety H3d: Individuals who report more frequent 'Social Media' sources exposure will perceive a higher level of information anxiety H3e: Individuals who report more frequent 'Other Internet Sources' exposure will perceive a higher level of information anxiety …”
Section: Theoretical Foundationmentioning
confidence: 99%